Numerical treatment for mathematical model of farming awareness in crop pest management - Anwar, Nabeela; Ahmad, Iftikhar; Kiani, Adiqa Kausar; Shoaib, Muhammad; Raja, Muhammad Asif Zahoor (Frontiers in Applied Mathematics and Statistics, 2023)
The most important factor for increasing crop production is pest and pathogen resistance, which has a major impact on global food security. Pest management also emphasizes the need for farming awareness. A high crop yield is ultimately achieved by protecting crops from pests and raising public awareness of the devastation caused by pests. In this research, we will explore at the dynamic impacts of nonlinear delayed crop pest management (CPM) systems supervised by ODEs, which emphasize the multifaceted and generally unforeseen interactions between crops and pests, rehabilitation strategies, and environmental factors across time. The nonlinear delayed CPM model incorporated the four compartments: crop biomass density (B(t)), susceptible pest density (S(t)), infected pest density (I(t)) and population awareness level (A(t)). The approximate solutions for the four compartments B(t), S(t), I(t), and A(t) are determined by the implementation of sundry scenarios generated with the variation in crop biomass growth rate, rate of pest attacks, pest natural death rate, disease associated death rate and memory loss of aware people, by means of exploiting the strength of the Adams (ADS) and explicit Runge-Kutta (ERK) numerical solvers. Comparative analysis of the designed approach is carried out for the dynamic impacts of the nonlinear delayed CPM model in terms of numerical outcomes and simulations based on sundry scenarios.